Grain-oriented electrical steel sheet and its manufacturing method

A controlled composition and annealing process for grain-oriented electrical steel sheets address issues of Goss orientation and core loss, resulting in a steel sheet with improved magnetic properties and surface quality, achieving low iron loss and uniformity.

JP2024546161AInactive Publication Date: 2024-12-17POHANG IRON & STEEL CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024536331
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-17
Filing Date
2022-12-16
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing methods for producing ultra-thin grain-oriented electrical steel sheets face challenges in achieving stable Goss orientation, uniform grain growth, and low core loss while maintaining excellent surface properties, due to issues with precipitate control, coating uniformity, and magnetic property deviations.

Method used

A specific composition of elements (Si, C, Al, Mn, N, Sn, Cr, P, Sb) in the steel, combined with controlled annealing processes, including rapid heating and staged oxidation, to form a uniform oxide layer and fine crystal grains, ensuring low iron loss and magnetic improvement.

Benefits of technology

The method results in a grain-oriented electrical steel sheet with reduced core loss deviation, improved magnetic properties, and enhanced surface quality, achieving an average iron loss of 0.80 W/kg or less and a thickness of 0.20 mm or less.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024546161000001_ABST
    Figure 2024546161000001_ABST
Patent Text Reader

Abstract

To provide ultra-thin grain oriented electrical steel sheet with improved magnetic properties and excellent surface characteristics, and reduced iron loss deviation. The present invention relates to a base material including, by weight, 2.5 to 4.0% Si, 0.005% or less C, 0.015 to 0.040% Al, 0.04 to 0.15% Mn, 0.005% or less N, 0.03 to 0.10% Sn, 0.05 to 0.2% Cr, 0.010 to 0.050% P, and 0.01 to 0.05% Sb, with the remainder being Fe and other unavoidably mixed impurities, and a metal oxide layer disposed on the base material, and the average core loss (W 17 / 50 ) is 0.80 W / kg or less, and the maximum luminous intensity ratio of the metal oxide layer satisfies the following formula 1. <Formula 1> I(Cr) / I_max(Mg)≦2% (In the above formula 1, I(Cr) is the Cr intensity in the metal oxide layer, and I_max(Mg) means the maximum luminescence intensity of Mg in the metal oxide layer)
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a grain-oriented electrical steel sheet and a manufacturing method thereof. [Background technology]

[0002] Grain-oriented electrical steel sheets are used as iron core materials for transformers, electric motors, generators, and other stationary electronic devices. The final grain-oriented electrical steel sheet products have a texture in which the crystal grains are oriented in the (110)

[0001] direction, and therefore have excellent magnetic properties in the rolling direction, making them suitable for use as iron core materials for transformers, electric motors, generators, and other electronic devices. Low iron loss is required to reduce energy loss, and high magnetic flux density is required to reduce the size of power generating equipment.

[0003] Currently, there is a worldwide trend toward energy conservation and the development of highly efficient products in order to reduce CO2 emissions and address global warming. Demand is increasing for highly efficient electrical equipment that can save electrical energy, and social demand is growing for the development of grain-oriented electrical steel sheets with superior low iron loss properties. As a result, much research and development is being conducted to reduce the iron loss of grain-oriented electrical steel sheets. One of the effective methods for reducing iron loss is the technology of refining secondary recrystallized grains. Refining secondary recrystallized grains reduces the size of the magnetic domains in the steel sheet, which reduces heat loss due to eddy currents caused by magnetic wall movement when the steel sheet is magnetized.

[0004] The iron loss of the grain-oriented electrical steel sheet can be divided into hysteresis loss and eddy current loss. Various methods have been proposed to reduce the eddy current loss, such as increasing the specific resistivity or reducing the sheet thickness of the product. The method of reducing the sheet thickness of the product is difficult because grain-oriented electrical steel sheet, which is a difficult-to-roll product, must be rolled into an extremely thin product. However, the biggest problem in producing an extremely thin product with very low iron loss characteristics is that it is very difficult to increase the concentration of the Goss orientation, which is the secondary recrystallization structure of the grain-oriented electrical steel sheet, as the thickness becomes thinner.

[0005] The hysteresis loss occurs when the movement of the magnetic domain walls is hindered by fine precipitates and inclusions, so the contents of components such as C, N, O, and S in the base material of the final product must be kept extremely low. As the Goss concentration increases, the core loss decreases. As the thickness of the product becomes thinner, the precipitates dissipate faster from the surface during the secondary recrystallization annealing process, especially in the section where secondary recrystallization of the Goss orientation occurs, making it difficult to maintain the texture and grain growth inhibition for the growth of the Goss orientation. This is a problem that directly affects the magnetic properties of the product, as it makes the secondary recrystallization phenomenon of the accurate Goss orientation unstable and non-uniform in ultra-thin products, resulting in non-uniform secondary crystal grain size or the formation of fine crystal grains with poor orientation concentration in some areas, making it difficult to ensure low iron loss properties. As the product becomes thinner, the ratio of the coating layer to the total product thickness increases. As the base coating becomes thicker, the ratio of the coating layer increases, which can reduce core loss.

[0006] As a method to overcome the precipitation loss, a method was proposed in which the N2 gas ratio was increased during the secondary recrystallization annealing process to prevent precipitation loss, but this had the problem of inducing surface defects such as nitrogen release holes on the surface of the product plate. A manufacturing method using the simultaneous decarburization-nitriding method was also proposed. This method utilizes the difference between the surface grain size and the central layer grain size when manufacturing decarburized plate using the simultaneous decarburization-nitriding method, and it was proposed that this difference needs to be controlled within a certain range. Also, a method of using segregation elements such as Sb, Sn, and P has been proposed. The inclusion of the segregation elements can dramatically improve magnetic properties and can be used as a supplementary inhibitor to compensate for precipitation loss during the manufacture of ultra-thin products. However, the method of adding the segregation elements has a problem that ultra-thin rolling becomes difficult when the segregation elements are added in excessive amounts. Furthermore, when the segregation elements are added in excess, the oxide layer becomes uneven and thin, which leads to inferior base coating properties, and the side effect of causing precipitation loss makes it difficult to stably ensure magnetic properties.

[0007] In addition, a method of adjusting the oxidation ability and nitriding treatment of the front end in the first recrystallization annealing process when manufacturing ultra-thin products has been proposed. However, there is a problem that the influence of precipitation loss is very sensitive in the manufacturing process of ultra-thin products. Also, a method was proposed in which chromium (Cr) was added to the slab and the amount of nitriding gas input at the front and rear ends was adjusted during the first recrystallization annealing process. However, this method maintained a uniform amount of nitrogen in the thickness direction of the steel sheet, but aluminum nitride (AlN) precipitates were distributed unevenly, resulting in a problem that deviations in magnetic properties still exist. In addition, the addition of chromium resulted in the formation of a chromium oxide layer, which became deeper and the thickness of the base coating became thicker, making it difficult to control oxidation and nitriding, and increasing the proportion of the coating layer in the product, which increased the hysteresis loss of thin products.

[0008] During the primary recrystallization annealing, decarburization and nitriding reactions take place in the surface layer of the steel sheet. The speed and timing of decarburization and nitriding depend on the shape of the oxide layer formed in the surface layer. The depth and composition of the oxide layer formed during the primary recrystallization annealing process vary subtly depending on the furnace atmosphere (temperature and oxidizing power), the content of the steel components, and the surface shape. In particular, the addition of elements such as Sb, Sn, and Cr changes the behavior of the oxide layer formation depending on the amount added, which ultimately affects the characteristics of the product, so the optimal conditions must be derived depending on the product characteristics. Summary of the Invention [Problem to be solved by the invention]

[0009] The technical problem to be solved by the present invention is to provide an extremely thin grain oriented electrical steel sheet having improved magnetic properties and excellent surface characteristics, and reduced iron loss deviation. Another technical problem to be solved by the present invention is to provide a method for manufacturing a grain-oriented electrical steel sheet having the above-mentioned advantages. [Means for solving the problem]

[0010] The grain-oriented electrical steel sheet of the present invention comprises, by weight%, a base material comprising 2.5 to 4.0% Si, 0.005% or less C, 0.015 to 0.040% Al, 0.04 to 0.15% Mn, 0.005% or less N, 0.03 to 0.10% Sn, 0.05 to 0.2% Cr, 0.010 to 0.050% P, and 0.01 to 0.05% Sb, with the remainder being Fe and other unavoidably mixed impurities; and a metal oxide layer disposed on the base material, and has an average core loss (W 17 / 50 ) is 0.80 W / kg or less, and the maximum luminous intensity ratio of the metal oxide layer satisfies the following formula 1. <Expression 1> I(Cr) / I_max(Mg)≦2% (In the above formula 1, I(Cr) is the Cr intensity in the metal oxide layer, and I_max(Mg) means the maximum luminescence intensity of Mg in the metal oxide layer.)

[0011] The steel plate may contain, by weight, S: 0.01 weight % or less (except 0%), V: 0.002 to 0.01 weight %, and Ti: 0.002 to 0.010 weight %. The steel sheet is preferably a grain-oriented electrical steel sheet having an iron loss deviation of 0.07 or less. The steel sheet is preferably a grain-oriented electrical steel sheet having a thickness of 0.2 mm or less.

[0012] The method for producing grain-oriented electrical steel sheet of the present invention includes the steps of hot rolling a steel slab containing, by weight, 2.5-4.0% Si, 0.03-0.09% C, 0.015-0.040% Al, 0.04-0.15% Mn, 0.002-0.012% N, 0.03-0.10% Sn, 0.05-0.2% Cr, 0.010-0.050% P, and 0.01-0.05% Sb, with the balance being Fe and other unavoidably mixed impurities; The method includes the steps of cold rolling a cold-rolled steel sheet, performing a first recrystallization annealing on the cold-rolled cold-rolled steel sheet, and performing a second recrystallization annealing on the steel sheet after the first recrystallization annealing, the first recrystallization annealing step including a temperature rise step, a first crack step, and a second crack step, the temperature rise step being performed in an oxidizing atmosphere having an oxidation ability of 0.5 to 2.0, the first crack step being performed in an atmosphere having an oxidation ability controlled to a range of less than 0.5, and the second crack step being performed in an atmosphere having an oxidation ability controlled to a range of 0.5 or more.

[0013] The steel slab may contain, by weight, S: 0.01% or less (except 0%), V: 0.002 to 0.01% by weight, and Ti: 0.002 to 0.010% by weight. The first recrystallization annealing step is preferably performed at a rate of 100° C. / s or more. The first recrystallization annealing step may include a rapid heating step at a temperature of 250 to 700°C. The first cracking stage and the second cracking stage are preferably carried out at a temperature of 800 to 900°C. It is preferable that the method includes a step of heating the steel slab to 1,230° C. or less prior to the step of hot rolling the steel slab. Effect of the Invention

[0014] According to the present invention, by controlling the steel composition, it is possible to provide a grain-oriented electrical steel sheet having excellent yield strength, excellent surface characteristics, and little iron loss deviation even in an extremely thin grain-oriented electrical steel sheet, which has a magnetic improvement effect, and excellent surface characteristics. A method for producing a grain-oriented electrical steel sheet according to another embodiment of the present invention can provide a method for producing a grain-oriented electrical steel sheet having the above-mentioned advantages. [Brief description of the drawings]

[0015] [Figure 1] 1 shows a grain oriented electrical steel sheet according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Terms such as first, second, and third are used to describe various parts, components, regions, layers, and / or sections, but are not limited thereto. These terms are used only to distinguish one part, component, region, layer, or section from another part, component, region, layer, or section. Thus, a first part, component, region, layer, or section described below may be referred to as a second part, component, region, layer, or section without departing from the scope of the present invention. The terminology used herein is merely for the purpose of referring to particular embodiments and is not intended to limit the present invention. As used herein, the singular form includes the plural form unless the phrase clearly indicates otherwise. As used in the specification, the meaning of "comprising" embodies the specified features, regions, integers, steps, operations, elements, and / or components and does not exclude the presence or addition of other features, regions, integers, steps, operations, elements, and / or components. When an element is referred to as being "on" or "on" another element, this means that it is immediately on or above the other element, or there may be other elements between them. In contrast, when an element is referred to as being "directly on" another element, there are no other elements between them.

[0017] Unless otherwise defined, all terms, including technical and scientific terms, used herein have the same meaning as commonly understood by a person of ordinary skill in the art to which the present invention belongs. Terms defined in commonly used dictionaries are additionally interpreted to have a meaning consistent with the relevant technical literature and the currently disclosed content, and are not interpreted in an ideal or very formal sense unless otherwise defined. Moreover, unless otherwise specified, % means % by weight, and 1 ppm is 0.0001% by weight. In an embodiment of the present invention, the term "additionally contain an additional element" refers to the addition of an additional amount of the additional element in place of the remaining iron (Fe). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to exemplary embodiments thereof, so that those skilled in the art will be able to easily practice the present invention. However, the present invention may be embodied in many different forms and is not limited to the embodiments set forth herein.

[0018] FIG. 1 shows a grain oriented electrical steel sheet 100 according to one embodiment of the present invention. 1, a grain-oriented electrical steel sheet 100 according to an embodiment of the present invention includes a base material 110 and a metal oxide layer 120 disposed on the base material 110. The base material 110 includes, by weight, 2.5-4.0% Si, 0.03-0.09% C, 0.015-0.040% Al, 0.04-0.15% Mn, 0.002-0.012% N, 0.03-0.10% Sn, 0.05-0.2% Cr, 0.010-0.050% P, and 0.01-0.05% Sb, with the remainder being Fe and other unavoidably mixed impurities. The reasons for limiting the alloy components are explained below. In the following, weight percent may be expressed as percent.

[0019] Silicon (Si): 2.5-4.0% Silicon (Si) increases the resistivity of grain-oriented electrical steel sheet material and reduces core loss. The silicon content is preferably 2.5 to 4.0%, more preferably 3.0 to 3.5%. If the upper limit of the range is exceeded, the brittleness of the steel increases, the toughness decreases, and the sheet breakage rate during rolling increases, the weldability deteriorates, and the cold rolling operation is burdened, and the sheet temperature required for pass aging during cold rolling does not reach, making secondary recrystallization unstable.If the lower limit of the range is exceeded, the resistivity decreases, and iron loss increases.

[0020] Carbon (C): 0.03~0.09% Carbon (C) is an element that induces the formation of austenite phase, and an increase in carbon content activates the ferrite-austenite phase transformation during the hot rolling process, and increases the elongated hot strip structure formed during the hot rolling process, suppressing the growth of ferrite grains during the hot rolled sheet annealing process. In addition, an increase in the carbon content increases the elongated hot strip structure, which has higher strength than the ferrite structure, and refines the initial grains of the hot rolled sheet annealing structure, which is the structure at the start of cold rolling, improving the texture after cold rolling and increasing the Goss fraction. The increase in the Goss fraction is due to the increase in the pass aging effect during cold rolling due to the residual carbon present in the steel sheet after hot rolled sheet annealing, which increases the Goss fraction in the primary recrystallized grains. The carbon content is preferably 0.03 to 0.09%, more preferably 0.05 to 0.070%. If the carbon content is out of the upper limit of the range, the decarburization annealing time during decarburization nitriding annealing becomes long, which reduces productivity. In addition, if decarburization at the beginning of heating is insufficient, the primary recrystallized grains become non-uniform, which makes the secondary recrystallization unstable. In addition, the magnetic properties become inferior due to magnetic aging. The carbon is removed by decarburization during the primary recrystallization annealing process, and the base material 110 in the finally manufactured grain-oriented electrical steel sheet 100 preferably contains 0.005% or less, more preferably 0.003%.

[0021] Aluminum (Al): 0.015-0.040% Aluminum (Al) combines with nitrogen (N) to precipitate as aluminum nitride (AlN), and forms fine precipitates of (Al,Si,Mn)N and nitrides in the form of AlN during annealing for decarburization and nitriding, which can play a strong role in inhibiting grain growth. The aluminum content is preferably 0.015-0.040%. More preferably, the aluminum content is in the range of 0.020-0.038%. If the aluminum content is outside the upper limit of the range, the precipitates grow coarsely, which reduces the grain growth inhibition effect, whereas if the aluminum content is outside the lower limit of the range, the number and volume fraction of precipitates formed are low, which in turn reduces the grain growth inhibition effect.

[0022] Manganese (Mn): 0.04-0.15% Manganese (Mn), like silicon (Si), has the effect of increasing resistivity and reducing iron loss. In addition, manganese, along with silicon, reacts with nitrogen introduced by nitriding to form (Al,Si,Mn)N precipitates, which inhibit the growth of primary recrystallized grains and cause secondary recrystallization. Manganese also forms sulfide precipitates together with copper (Cu), improving the uniformity of primary recrystallized grains and acting as an auxiliary inhibitor in the formation of secondary recrystallization. The manganese content is preferably 0.04 to 0.15%, more preferably 0.05 to 0.10%. If the manganese content is out of the upper limit of the range, the slab reheating temperature must be increased to adjust the (Cu, Mn)S fine precipitates, and if the slab reheating temperature is increased, the primary recrystallized grains become very fine, so the temperature of the primary recrystallization annealing must be increased beyond the range, which may cause non-uniform grains. In addition, a large amount of (Fe, Mn) and Mn oxides other than Fe2SiO4 are formed on the steel sheet surface, which impedes the formation of a base coating during secondary recrystallization annealing and reduces surface quality, and the primary recrystallization annealing process induces non-uniformity in the phase transformation between ferrite and austenite, resulting in non-uniform sizes of primary recrystallization grains and thus unstable secondary recrystallization. If the manganese content falls outside the lower limit of the range, the effect of reducing iron loss described above is not achieved, and the formation of the (Al, Si, Mn)N precipitates inhibits the growth of primary recrystallization grains, resulting in no effect of inducing secondary recrystallization.

[0023] Nitrogen (N): 0.002-0.012% Nitrogen (N) is an element that reacts with aluminum (Al) and the like to refine crystal grains. When these elements are appropriately distributed, they properly refine the structure after cold rolling to ensure an appropriate primary recrystallization grain size. The nitrogen content is preferably 0.0020 to 0.012%, more preferably 0.0025 to 0.010%. If the nitrogen content is outside the upper limit of the range, the primary recrystallized grains are excessively fined, and thus the fine grains may form secondary recrystallization in an undesirable orientation, deteriorating the magnetic properties. On the other hand, if the nitrogen content is outside the lower limit of the range, the effect of inhibiting primary recrystallization becomes insignificant, and the effect of inhibiting grain growth cannot be obtained. Since the nitrogen is partially removed during the secondary recrystallization annealing process, the nitrogen content of the base material 110 of the final grain-oriented electrical steel sheet 100 is preferably 0.005% or less, more preferably 0.003% or less.

[0024] Antimony (Sb): 0.01-0.05% Antimony (Sb) increases the number of crystal grains with Goss orientation generated during the cold rolling process, and improves the fraction of crystal grains with Goss orientation in the primary recrystallization texture. It also segregates at the primary recrystallization grain boundaries and increases the secondary recrystallization start temperature of crystal grains with Goss texture during secondary recrystallization high-temperature annealing, thereby enabling a secondary recrystallization fine texture with excellent integration to be obtained, thereby increasing magnetic flux density. The content of antimony is preferably 0.01 to 0.05%, more preferably 0.020 to 0.045%. If the content of antimony is outside the upper limit of the range, the size of the primary recrystallized grains becomes too small, the secondary recrystallization start temperature becomes low, and the magnetic properties may deteriorate, or the suppression force against grain growth becomes too strong, and the secondary recrystallization may not occur. On the other hand, if the content of antimony is outside the lower limit of the range, the effect of improving the fraction of crystal grains having the Goss orientation is not achieved, and the secondary recrystallized fine structure cannot be obtained, and the effect of increasing the magnetic flux density is not achieved.

[0025] Tin (Sn): 0.03 to 0.10% Tin (Sn) is a grain boundary segregation element that impedes the movement of grain boundaries and is therefore known as a grain growth inhibitor. In addition, by increasing the fraction of Goss oriented grains in the primary recrystallization texture, the number of Goss oriented nuclei that grow into the secondary recrystallization texture increases. In addition, the more tin is added, the smaller the size of the secondary recrystallization microstructure becomes. As the size of the secondary recrystallization microstructure decreases, the smaller the grain size becomes, which reduces eddy current loss, and therefore reduces iron loss in the final product. In addition, the tin plays an important role in suppressing grain growth through segregation at grain boundaries, which not only improves the suppression effect of suppressing the driving force of grain growth of the refined primary recrystallization microstructure, but also prevents the phenomenon in which particles such as (Al, Si, Mn)N and AlN, which cause a grain growth suppression effect, become coarse during the high-temperature annealing process for forming the secondary recrystallization texture, thereby reducing the suppression effect of grain growth. The tin content is preferably 0.03 to 0.10%, and more preferably 0.03 to 0.09%. If the tin content is outside the upper limit of the range, the grain growth inhibitory force increases excessively, and the grain size of the primary recrystallized microstructure must be reduced to relatively increase the grain growth driving force, so that decarburization annealing must be performed at a low temperature. As a result, the oxide layer cannot be appropriately controlled, and a good surface cannot be obtained. In addition, in terms of mechanical properties, excessive segregation of critical segregation elements increases brittleness, which may cause plate breakage during the manufacturing process. Meanwhile, if the tin content is outside the lower limit of the range, the effect of the addition of tin may not be achieved.

[0026] Chromium (Cr): 0.05~0.2% Chromium (Cr) is an element that promotes the formation of oxides, and adding chromium (Cr) within a certain range suppresses the formation of a dense oxide layer in the surface layer and promotes the formation of a fine oxide layer in the depth direction. The chromium, when added together with the antimony and the tin, promotes the formation of an oxide layer in the depth direction by increasing the formation of FeCr2O4 in the surface layer of the oxide layer. The chromium content is preferably in the range of 0.05 to 0.20%. In the case of chromium, if it is added to a thin product of 0.20mmt or less, a thick oxide layer is formed, which changes the composition of the oxide layer and affects decarburization and nitriding, so if it is not properly controlled in the decarburization-nitriding annealing process, it becomes difficult to properly control the primary recrystallized grain size and precipitate formation, which may induce magnetic deviation in ultra-thin grain-oriented electrical steel sheets. Also, a chromium (Cr)-enriched layer is formed in the base coating layer of the final product sheet, and in the case of thin grain-oriented electrical steel sheets, the base coating layer becomes thicker and increases non-uniformity, which causes iron loss deviation.

[0027] Phosphorus (P): 0.010-0.050% Phosphorus (P) is an element that exhibits effects similar to those of tin (Sn) and antimony (Sb), and plays an auxiliary role in preventing grain boundary migration by segregating at the grain boundaries and at the same time suppressing grain growth. <001> It has an effect of improving the texture. The phosphorus content is preferably in the range of 0.010 to 0.050%, and more preferably in the range of 0.015 to 0.045%. If the phosphorus content is too high, there is a problem that brittleness increases and rollability is significantly reduced, whereas if the phosphorus content is too low, there is a problem that the effect of adding phosphorus is not achieved. In one embodiment, the grain-oriented electrical steel sheet 100 may further include, in weight percent, sulfur (S): 0.01 weight percent or less (excluding 0%), vanadium (V): 0.002 to 0.01 weight percent, and titanium (Ti): 0.002 to 0.010 weight percent.

[0028] Sulfur (S): 0.010% or less Sulfur (S) is an element that has a high solid solution temperature during hot rolling and is subject to severe segregation, so it is preferable to avoid its inclusion as much as possible, but it is one of the inevitable impurities that are included during steelmaking. Sulfur (S) is also an element that forms (Mn, Cu)S and affects the uniformity of primary recrystallized grains. The content of sulfur is preferably 0.010% by weight or less, more preferably 0.0010 to 0.0080%.

[0029] Titanium (Ti): 0.002 to 0.010% Titanium (Ti) is an element that forms nitrides, and becomes titanium nitride (TiN) before hot rolling, reducing the nitrogen content and suppressing grain growth by finely precipitating. The titanium content is preferably in the range of 0.002~0.010%, and within this range, the effect of suppressing grain growth by forming titanium nitride precipitates and the effect of reducing the deviation of grain size within the coil by reducing fine precipitates of aluminum nitride (AlN) are obtained.

[0030] Vanadium (V): 0.002 to 0.01% Vanadium (V) is a carbide and nitride forming element that acts to suppress grain growth by finely precipitating. The vanadium content is preferably in the range of 0.002~0.01%, and within this range, the effect of suppressing grain growth by forming fine precipitates is realized, thereby reducing the grain size deviation within the coil.

[0031] In one embodiment, at least one of titanium (Ti) and vanadium (V) may be further included in an amount of 0.002 to 0.010 wt%. When the vanadium and titanium are included alone, each of them may be included in an amount of 0.002 to 0.010 wt%, and when the vanadium and titanium are included simultaneously, the total amount of the vanadium and the titanium may be 0.002 to 0.010 wt%. More specifically, the content of the titanium and the vanadium is more preferably in the range of 0.0030 to 0.0070 wt%.

[0032] In one embodiment, in addition to the above elements, the grain-oriented electrical steel sheet 100 may contain unavoidable impurities such as Zr, Cu, Ni, and Mo. The above impurities are strong carbonitride forming elements and are preferably not added as much as possible, and each should be contained in an amount of 0.01 wt % or less. The balance includes iron (Fe). Inevitable impurities are also included. Inevitable impurities refer to impurities that are inevitably mixed in during the steelmaking and manufacturing process of the grain-oriented electrical steel sheet. As unavoidable impurities are widely known, a detailed description will be omitted. In one embodiment of the present invention, the addition of elements other than the above-mentioned alloy components is not excluded, and various elements may be included within a range that does not harm the technical concept of the present invention. When an additional element is further included, it is included in place of the balance Fe.

[0033] The metal oxide layer 120 of the present invention is disposed on the host material 110. The metal oxide layer 120 can include materials such as, for example, magnesium (Mg), aluminum (Al), boron (B), antimony (Sb), tin (Sn), molybdenum (Mo), tungsten (W), and chromium (Cr). The maximum emission intensity ratio of the metal oxide layer 120 of the present invention satisfies the following formula 1. <Expression 1> I(Cr) / I_max(Mg)≦2% (In the above formula 1, I(Cr) is the Cr intensity in the metal oxide layer, and I_max(Mg) means the maximum luminescence intensity of Mg in the metal oxide layer.)

[0034] The maximum emission intensity can be obtained by measuring the ratio of the maximum intensity of magnesium (Mg) component to the intensity of chromium (Cr) at the same thickness through elemental analysis of the metal oxide layer in the thickness direction using a glow discharge surface analysis method. When the value of I(Cr) / I_max(Mg) is 2% or less, the base coating layer is dense and uniform, which is advantageous for uniform formation of the coating layer.On the other hand, when the value of I(Cr) / I_max(Mg) is more than 2%, the effect of the Cr-rich layer increases the non-uniformity of the coating layer, which causes iron loss deviation.

[0035] The grain-oriented electrical steel sheet 100 of the present invention may have a thickness of 0.20 mm or less. If the thickness of the grain-oriented electrical steel sheet 100 is more than 0.20 mm, the effect of coating non-uniformity due to Cr enrichment on iron loss deviation is reduced. The average core loss (W 17 / 50 ) is preferably 0.80W / kg or less. 17 / 50 ) is the magnitude of iron loss (W / kg) induced under the conditions of 1.7 Tesla and 50 Hz. By satisfying the above average iron loss value, it is possible to provide a grain-oriented electrical steel sheet 100 having excellent magnetic properties.

[0036] The iron loss deviation of the grain-oriented electrical steel sheet 100 of the present invention is preferably 0.07 or less. The iron loss deviation means the deviation of the iron loss value. By satisfying the iron loss deviation value of 0.07 or less, it is possible to provide a grain-oriented electrical steel sheet 100 having excellent magnetic properties.

[0037] A method for producing grain-oriented electrical steel sheet of the present invention includes the steps of hot rolling a steel slab containing, in weight %, 2.5 to 4.0% Si, 0.03 to 0.09% C, 0.015 to 0.040% Al, 0.04 to 0.15% Mn, 0.002 to 0.012% N, 0.03 to 0.10% Sn, 0.05 to 0.2% Cr, 0.010 to 0.050% P, and 0.01 to 0.05% Sb, with the remainder being Fe and other unavoidably mixed impurities, cold rolling the hot rolled hot rolled steel sheet, performing primary recrystallization annealing on the cold rolled cold rolled steel sheet, and performing secondary recrystallization annealing on the steel sheet after the primary recrystallization annealing is completed. The detailed description of the steel slab is the same as that of the grain-oriented electrical steel sheet described above to the extent that it does not contradict, so duplicated description will be omitted.

[0038] Prior to the hot rolling of the steel slab, the steel slab may be heated to 1,230° C. or less. Specifically, the steel slab may be heated to a temperature in the range of 1,130 to 1,200° C. The steel slab is heated to partially dissolve precipitates. Also, the columnar crystal structure of the slab is prevented from growing coarsely, which prevents cracks from occurring in the width direction of the plate during the subsequent hot rolling process, thereby improving the yield. If the temperature range in the steel slab heating step is too high, the surface of the slab may melt, which may require repairs of the heating furnace and shorten the life of the heating furnace. The present invention also allows the continuous cast steel slab to be hot rolled as is without performing the step of heating the steel slab.

[0039] The step of hot rolling the steel slab can produce a hot rolled sheet with a thickness of 1.8 to 2.3 mm. The step of hot rolling the steel slab of the present invention further includes a step of cooling and coiling after the rolling is completed, taking into consideration the rolling load. The method may include a step of annealing the hot-rolled steel sheet after hot-rolling the steel slab. The step of annealing the hot-rolled steel sheet is performed by heating the steel sheet to a temperature of 950 to 1,100°C, cracking the steel sheet at a temperature of 850 to 1,000°C, and then cooling the steel sheet.

[0040] The step of cold rolling the hot rolled steel sheet may be performed through one cold rolling pass or through multiple passes. In the step of cold rolling the hot rolled steel sheet of the present invention, it is preferable that at least one of the rolling passes is warm rolling at a temperature of 200 to 300°C. The warm rolling provides a pass aging effect, and the cold rolled steel sheet may be manufactured to have a final thickness of 0.18 to 0.20 mm. The cold rolled cold rolled steel sheet is subjected to decarburization and recrystallization of the deformed structure during the primary recrystallization annealing process, and nitriding treatment using nitriding gas. The step of subjecting the cold-rolled steel sheet to primary recrystallization annealing may include a temperature rise step, a first crack step, and a second crack step. Specifically, the step of subjecting the cold-rolled steel sheet to primary recrystallization annealing may include rapid heating in the temperature rise step, followed by decarburization and nitriding annealing including the first crack step and the second crack step.

[0041] The temperature increasing step is a step of heating the cold rolled steel sheet to a crack temperature in the first crack stage. The temperature increasing step of the present invention may be performed by rapidly heating the steel sheet at a temperature of 250 to 700° C. and at a heating rate of 100° C. / s or more. During the rapid heating, the oxidation ability (P H20 / P H2 It is preferable to carry out the heating in an oxidizing atmosphere having an oxidizing ability (P H20 / P H2 ) can be performed in an oxidizing atmosphere of 1.0 to 2.0. During the rapid heating mentioned above, the oxidizing ability (P H20 / P H2 If the value of oxidizing ability (P) exceeds the upper limit, there is a problem that the decarburization and nitriding reactions are inhibited due to the formation of an excessive oxide layer. H20 / P H2 If the value of (a) is outside the lower limit, it becomes difficult to uniformly control the oxide layer formed in the subsequent processes, in particular, to control the Cr oxide layer. The first cracking step is a step of cracking the steel sheet that has been heated through the temperature increasing step in a temperature range of 700 to 850°C. In the present invention, the first cracking step is performed with an oxidation potential in the range of less than 0.5. Specifically, the first cracking step is preferably performed with an oxidation potential in the range of 0.1 to 0.5. Specifically, the oxidation potential is more preferably in the range of 0.3 to 0.5.

[0042] When the first cracking stage is performed within the range of the oxidation ability, there is an advantage that it is possible to uniformly control the oxide layer, specifically, to uniformly control the formation of the Cr oxide layer and to uniformly control the decarburization-nitriding reaction. When the range of the oxidation ability deviates from the upper limit of the first cracking stage, there is a problem that the decarburization-nitriding reaction is inhibited due to the formation of an excessive oxide layer. When the range of the oxidation ability deviates from the lower limit of the first cracking stage, there is a problem that it becomes difficult to uniformly control the oxide layer formed, specifically, to control the Cr oxide layer. The second cracking stage is a stage in which the steel sheet that has been through the first cracking stage is cracked at a temperature range of 800 to 900° C. The first cracking stage and the second cracking stage can be distinguished according to the oxidation degree of the atmosphere.

[0043] In one embodiment, the oxidation potential in the second cracking step is in the range of 0.5 or more. In one embodiment, the oxidation potential in the second cracking step is preferably in the range of 0.5 to 0.8. More preferably, the oxidation potential is in the range of 0.5 to 0.7. When the second cracking stage is performed within the range of the oxidation capacity, there is an advantage in uniform control of the decarburization-nitriding reaction in relation to the first cracking stage. When the range of the oxidation capacity in the second cracking stage deviates from the upper limit, there is a problem that the decarburization-nitriding reaction is inhibited due to the formation of an excessive oxide layer. When the range of the oxidation capacity in the second cracking stage deviates from the lower limit, there is a problem that uniform control of the oxide layer and uniform control of the nitriding are difficult.

[0044] In one embodiment, at least one of the heating step, the first cracking step, and the second cracking step may be performed in an atmosphere containing at least one of hydrogen and nitrogen. In one embodiment, at least one of the heating step, the first cracking step, and the second cracking step may be performed by adding ammonia to an atmosphere containing at least one of hydrogen and nitrogen. In this way, in the primary recrystallization annealing process, decarburization and nitriding are simultaneously performed through the above-mentioned oxidation ability adjustment, and when the oxidation ability at the first crack stage and the oxidation ability at the second crack stage are different as described above, there is an advantage that the decarburization and nitriding reactions are uniformly controlled while the oxide layer, especially the Cr oxide layer, is uniformly controlled, and the fine structure of the decarburized sheet, the surface oxide layer, and precipitates are more uniformly formed.

[0045] The step of subjecting the steel sheet after the first recrystallization annealing to the second recrystallization annealing is to apply an annealing separator to the first recrystallized steel sheet and then perform a final annealing for a long time to cause the second recrystallization, so that the {110} plane of the steel sheet is parallel to the rolling surface, <001> {110} with orientation parallel to the rolling direction <001> The Goss texture can be formed. The annealing separator may be, for example, based on MgO, but this is a non-limiting example and various types of annealing separators can be used. Through the secondary recrystallization annealing, {110} <001> It forms texture, and the oxide layer formed during decarburization reacts with MgO to form a glassy film, which provides insulation and removes impurities that reduce magnetic properties.As a final annealing method, a mixture of nitrogen and hydrogen gas is supplied in the temperature rise section before the secondary recrystallization occurs to protect the nitrides, which act as grain growth inhibitors, allowing the secondary recrystallization to develop well, and after the secondary recrystallization is complete, it can be maintained in a 100% hydrogen atmosphere for a long period of time to remove impurities.

[0046] Hereinafter, the grain-oriented electrical steel sheet and the manufacturing method thereof according to the present invention will be described in detail with reference to the following examples and comparative examples. The following examples are provided for the purpose of explaining the present invention in detail, and the present invention is not limited thereto, and may be embodied in various forms. EXAMPLES

[0047] <Steel type> The following Table 1 shows the compositions of the main components of steel types A to E. The following Table 1 discloses steels that satisfy all of the composition ranges of the present invention.

[0048] [Table 1] From Table 1 above, it can be seen that steels A to E are all within the scope of the present invention.

[0049] <Steel plate characteristic measurement> Steel types A to E having the composition in Table 1 were vacuum melted, and then ingots were produced, and grain-oriented electrical steel sheets were produced under the production conditions in Table 2 below. Specifically, the ingots were produced, and then heated at a temperature of 1,150°C for 210 minutes, and then hot-rolled to produce hot-rolled steel sheets having a thickness of 2.0 mm. After pickling, the steel sheets were cold-rolled to a thickness of 0.20 mm or 0.18 mm at a single reduction of 90% or more. The cold-rolled steel sheet is rapidly heated from 250 to 700°C at a heating rate of 100°C / sec or more. H20 / P H2) was carried out under the conditions in Table 2 below. After that, during decarburization and nitriding annealing, the oxidation capacity was measured for the one-stage decarburization and two-stage decarburization nitriding processes under the oxidation capacity (P H20 / P H2 ) at 850°C for 180 seconds in a humid atmosphere and an ammonia mixed gas atmosphere so that the carbon content was 30 ppm or less and the total nitrogen content was 200 ppm or more.

[0050] The steel sheet that had undergone the decarbonitriding annealing heat treatment was coated with an annealing separator containing 95 wt% MgO and 25 wt% TiO in solid content, and then subjected to secondary recrystallization annealing in a coil shape. The secondary recrystallization annealing was performed in a mixed atmosphere of 25 vol% nitrogen and 75 vol% hydrogen up to 1,200°C, and after reaching 1,200°C, the atmosphere was maintained in 100% hydrogen for 10 hours or more, and then furnace cooled. Thereafter, an insulating coating layer-forming composition containing a mixed solution of metal phosphate and colloidal silica was applied and heat-treated to form an insulating coating layer. The maximum luminescence intensity ratio [I(Cr) / I_max(Mg)] and iron loss deviation measured for each condition can be seen in Table 2 below. The maximum luminescence intensity ratio was measured as the ratio of the maximum luminescence intensity of Mg to the Cr intensity of the metal oxide layer. Specifically, the maximum luminescence intensity was measured as the ratio of the maximum intensity of the Mg component to the Cr intensity ratio at the same thickness through elemental analysis of the metal oxide layer in the thickness direction using a glow discharge surface analysis method. The first-stage SDN oxidation capacity and second-stage SDN oxidation capacity in Table 2 below refer to the method of controlling inhibitors in the decarburization process after cold rolling.

[0051] [Table 2]

[0052] From Table 2 above, it can be seen that the inventive materials, in which the oxidation ability of the rapid heating and simultaneous decarbonitriding annealing was controlled within a control range, had a small emission intensity ratio of within 2% and excellent iron loss deviation. In contrast, it can be seen that the comparative materials, which deviated from the control range, had poor iron loss deviation due to non-uniform crystal grain size or a defective base coating. Specifically, it was confirmed that Comparative Examples 1 and 4 had a problem with non-uniform crystal grain size, and Comparative Examples 2, 3, 5, and 6 had a problem with a defective base coating layer.

[0053] The present invention is not limited to the above implementations and / or examples, and can be manufactured in various different forms, and a person skilled in the art to which the present invention pertains can understand that the present invention can be embodied in other specific forms without changing the technical concept or essential features of the present invention. Therefore, the implementations and / or examples described above should be understood to be illustrative in all respects and not limiting. [Explanation of symbols]

[0054] 100 grain-oriented electrical steel sheet 110 Base material 120 Metal oxide layer

Claims

1. A base material containing, in weight percent, 2.5 to 4.0 weight percent Si, 0.005 weight percent or less C, 0.015 to 0.040 weight percent Al, 0.04 to 0.15 weight percent Mn, 0.005 weight percent or less N, 0.03 to 0.10 weight percent Sn, 0.05 to 0.2 weight percent Cr, 0.010 to 0.050 weight percent P, and 0.01 to 0.05 weight percent Sb, with the balance being Fe and other unavoidably mixed impurities; and a metal oxide layer disposed on the base material; Average iron loss (W 17/50 ) is 0.80 W / kg or less, A grain-oriented electrical steel sheet, characterized in that the maximum luminous intensity ratio of the metal oxide layer satisfies the following formula 1. <Formula 1> I(Cr) / I_max(Mg)≦2% (In the above formula 1, I(Cr) is the Cr intensity in the metal oxide layer, and I_max(Mg) means the maximum luminescence intensity of Mg in the metal oxide layer.)

2. The grain-oriented electrical steel sheet according to claim 1, characterized in containing, by weight%, S: 0.01 weight % or less (excluding 0%), V: 0.002 to 0.01 weight %, and Ti: 0.002 to 0.010 weight %.

3. 2. The grain-oriented electrical steel sheet according to claim 1, characterized in that the iron loss deviation is 0.07 or less.

4. 2. The grain-oriented electrical steel sheet according to claim 1, wherein the thickness is 0.2 mm or less.

5. hot rolling a steel slab containing, in weight percent, 2.5-4.0% Si, 0.03-0.09% C, 0.015-0.040% Al, 0.04-0.15% Mn, 0.002-0.012% N, 0.03-0.10% Sn, 0.05-0.2% Cr, 0.010-0.050% P, and 0.01-0.05% Sb, with the balance being Fe and other unavoidably mixed impurities; cold rolling the hot-rolled steel sheet; A step of subjecting the cold-rolled steel sheet to a first recrystallization annealing; The steel sheet after the first recrystallization annealing is subjected to a second recrystallization annealing, The first recrystallization annealing step includes a temperature increase step, a first crack step, and a second crack step, The temperature rise step is carried out in an oxidizing atmosphere having an oxidizing power of 0.5 to 2.

0. The first cracking step is carried out in an atmosphere in which the oxidation potential is controlled to be less than 0.5; The second cracking step is carried out in an atmosphere having an oxidation ability controlled to a range of 0.5 or more.

6. The method for producing a grain-oriented electrical steel sheet according to claim 5, characterized in that the steel slab contains, by weight%, S: 0.01% or less (excluding 0%), V: 0.002 to 0.01% by weight, and Ti: 0.002 to 0.010% by weight.

7. The method of claim 5, wherein the first recrystallization annealing is performed at a rate of 100° C. / s or more.

8. 6. The method of claim 5, wherein the first recrystallization annealing step comprises a rapid heating step at a temperature of 250 to 700.degree. C.

9. The method of claim 5, wherein the first and second cracking steps are performed at a temperature of 800 to 900°C.

10. Prior to the step of hot rolling the steel slab, 6. The method of claim 5, further comprising the step of heating the steel slab at a temperature of 1,230° C. or less.

Citation Information

Patent Citations

  • Production of grain oriented silicon steel sheet with minimal iron loss and high magnetic flux density

    JP1998121135A

  • Production of grain oriented silicon steel sheet excellent in magnetic property

    JP2000034521A

  • Manufacture of grain oriented silicon steel sheet excellent in film characteristic and magnetic property

    JP2000096149A

  • Grain oriented silicon steel sheet excellent in coating film characteristic and magnetic property and its production

    JP2000355717A

  • Method for manufacturing grain-oriented silicon steel by single cold rolling.

    JP2011518947A